Raranga te Kete Aronui—Weaving the Basket: Continuing With Open, Flexible, and Distance Learning - Fields A; Hartnett M (Flexible Learning Association of New Zealand (FLANZ), 2020)
This issue of the Journal uses the metaphor of raranga te kete aronui (weaving the basket of the pursuit of knowledge) as it continues the conversation of developing areas of open, flexible, and distance learning (OFDL). It comes at a time when the COVID-19 pandemic has disrupted traditional face-to-face teaching in classrooms on a global scale, and the value of open, flexible, and distance learning has become starkly apparent. This issue has five articles which contribute to the ongoing knowledge presented in this issue. There are two articles based on educational theory: Higgins explores the theoretical history of OFDL, and the work of Nichols et al. is based on Mezirow’s 10 stages of transformative learning. Three research articles provide insight into a range of specific areas: Sime et al. use networked learning theory to investigate the design of a social exploration MOOC, Irons and Hartnett present exploratory research into the teaching of computational thinking in junior classrooms in New Zealand, and Nyugen describes the design and development of qualifications in early childhood education and care to meet a demand for New Zealand home-based early childhood educators to be qualified. These are all contributions to our weaving and filling of te kete aronui.
Keywords: educational theory; flexible learning; online learning; learning design